The relationships between nitrogen use efficiency and nitrogen input in crop production in Poland - Faber, Antoni; Jarosz, Zuzanna; Kopiński, Jerzy; Matyka, Mariusz (Polish Journal of Agronomy, 2016)
The study attempted to characterize Nitrogen Use Efficiency (NUE), nitrogen yield (Yn), and N balance (Nb = N surplus) depending on the dose of the total N fertilization (F = N dose in mineral fertilizers, natural fertilizers, or N from de- position). The study included basic crops in Poland in the years 1999–2014. The determination of the relationships between Yn, NUE, Nb, depending on F was performed using the elements of the methodology proposed by Lassaletta et al. (2014). The eva- luation of differences between the optimal NUE and the NUE obtained in this study was carried out using the lower limits of the optimal NUE = 70–90%, as proposed tentatively by the EU NEP (2014). The study indicates that in the period of 1999–2014, NUE of basic crops in Poland increased, achieving the weighted average value of 55%. This value was significantly decreased by low NUE of permanent grasslands (42%), which have the largest share (20.3%) in the structure of land use in Poland. It would, therefore, be recommendable to increase NUE on grasslands. The omission of permanent grassland in the analysis increased the we- ighted average NUE for basic crops on arable lands to the value of 60%. There were no differences found in the weighted average NUE values in the case of more intensive (60%) and more exten- sive (60%) crops. Assuming that there is a need to increase NUE to the lower level of the optimal value (70%), we concluded, on the basis of our results and discussion, that the most effective way to achieve it would be to improve the NUE of more inten- sive crops, especially of wheat, triticale and barley. These plants achieve higher grain yields, Yn, Ymax, and Yn gap. They also have a larger share in the crop structure in comparison with more extensive crops.